Digital Transformation on Competitive Advantage through Customer Experience in Indonesian Companies - Ervina Abdul Gani; Christian Herdinata; Liliana Dewi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Despite the rapid growth of digital transformation in Indonesia, many firms still face challenges such as limited digital literacy, unequal infrastructure, and high implementation costs, which hinder their ability to fully leverage technology to enhance customer experience and achieve a competitive advantage. Drawing on Dynamic Capability Theory, this research examines how digital transformation initiatives influence competitive advantage through enhanced customer experience in the context of a developing economy. The data for this research were collected using an online questionnaire of 350 managers and business leaders from Indonesian companies that have implemented digital transformation initiatives. The sampling criteria included companies with at least one digital transformation initiative implemented in the past two years and respondents with direct involvement in digital transformation programs. Using structural equation modeling for analysis, this study’s results reveal that digital transformation positively influences both directly and indirectly to competitive advantage through customer experience mediation. The findings of this study indicate that customer experience takes a significantly mediating role in translating digital transformation efforts into competitive advantages. Furthermore, the research demonstrates that despite implementation challenges in developing countries, companies can successfully leverage digital transformation to enhance their competitive position through improved customer experience.